Inhibition of inflammatory cells delays retinal degeneration in experimental retinal vein occlusion in mice - Jovanovic, Joël (Glia, 2019)
The role of microglia in retinal inflammation is still ambiguous. Branch retinal vein occlusion initiates an inflammatory response whereby resident microglia cells are activated. They trigger infiltration of neutrophils that exacerbate blood–retina barrier damage, regulate postischemic inflammation and irreversible loss of neuroretina. Suppression of microglia‐mediated inflammation might bear potential for mitigating functional impairment after retinal vein occlusion (RVO). To test this hypothesis, we depleted microglia by PLX5622 (a selective tyrosine kinase inhibitor that targets the colony‐stimulating factor‐1 receptor) in fractalkine receptor reporter mice (Cx3cr1 (gfp/+)) subjected to various regimens of PLX5622 treatment and experimental RVO. Effectiveness of microglia suppression and retinal outcomes including retinal thickness as well as ganglion cell survival were compared to a control group of mice with experimental vein occlusion only. PLX5622 caused dramatic suppression of microglia. Despite vein occlusion, reappearance of green fluorescent protein positive cells was strongly impeded with continuous PLX5622 treatment and significantly delayed after its cessation. In depleted mice, retinal proinflammatory cytokine signaling was diminished and retinal ganglion cell survival improved by almost 50% compared to nondepleted animals 3 weeks after vein occlusion. Optical coherence tomography suggested delayed retinal degeneration in depleted mice. In summary, findings indicate that suppression of cells bearing the colony‐stimulating factor‐1 receptor, mainly microglia and monocytes, mitigates ischemic damage and salvages retinal ganglion cells. Blood–retina barrier breakdown seems central in the disease mechanism, and complex interactions between different cell types composing the blood–retina barrier as well as sustained hypoxia might explain why the protective effect was only partial.